2020
DOI: 10.1111/obes.12356
|View full text |Cite
|
Sign up to set email alerts
|

The Wage Penalty for Married Women of Career Interruptions: Evidence from the 1970s and the 1990s

Abstract: The goal of this paper is to assess how the wage penalty for career interruptions by married women changed between the 1970s and the 1990s. We estimate the wage penalty for career interruptions using the work‐history model and PSID data. We use several approaches to control for various forms of endogeneity and selection bias. Our empirical results suggest that (i) the wage penalty for married women's career interruptions increased from 40.4% to 73.7% over the period, (ii) the ratio of the wage penalty for marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The empirical analysis in this paper relies on Wooldridge (1995), see Jones et al (2020) for an application to the estimation of the wage equation in the presence of labor participation interruptions. We follow Wooldridge (1995) to estimate a model where selection is on the decision of whether or not to invest in innovation.…”
Section: Empirical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical analysis in this paper relies on Wooldridge (1995), see Jones et al (2020) for an application to the estimation of the wage equation in the presence of labor participation interruptions. We follow Wooldridge (1995) to estimate a model where selection is on the decision of whether or not to invest in innovation.…”
Section: Empirical Analysismentioning
confidence: 99%
“…We follow Wooldridge (1995) to estimate a model where selection is on the decision of whether or not to invest in innovation. Using the notation in Jones et al (2020), the main equation to be estimated is where x 1it is observed for all firms, whereas x 2it is observed only for those firms that invest in innovation. The selection equation that determines whether y it is observed is therefore where z it includes x 1it and z 2it , observed for all firms.…”
Section: Empirical Analysismentioning
confidence: 99%